Las relaciones laborales e interpersonales entre los estamentos de la Universidad Técnica de Cotopaxi durante el período 2014-2015 - Ronquillo Catagña, Adriana Guadalupe (2015)
The research was aimed to solving caused problems by the lack communication between Cotopaxi Technical University dependences, the same that caused the deterioration on practice of values and a poor attention of institution´s internal and external customers. In the first research part was developed based on the need to improve labor relations of all who make the institution Cotopaxi Alma Mater; to create and preserve a work environment, quality and warmth….